An optically modulated radio frequency backscatter wireless data link - Cantú, H.; Ironside, Charlie; Romeira, B.; Kelly, A.; Figueiredo, J. (2013)
The paper reports on how a technique adapted from Radio Frequency Identity (RFID) tag systems is used to implement a low cost, low energy optical/wireless data link, using inexpensive, off-the-shelf components. We describe how the changes in impedance of an antenna-coupled photo-detector under optical illumination are used to encode binary data into a backscatter radio frequency (RF) wireless signal. The backscatter device consists of an 850 nm VCSEL source (OPTEK OPV302) directly modulated by data at 1 Mbit/s, which illuminates an unbiased photo-detector (Hamamatsu S5973-01) attached to the input port of an omnidirectional antenna. An interrogator is used at the carrier frequency of 1 GHz in order to extract the information from the modulated backscatter RF signal. The system is illustrated in Fig. 1. The pseudo-random bit sequence data (non-return to zero, 1.6 Vpp) is downloaded into an arbitrary waveform generator (AWG) that amplitude modulates the laser source illuminating the antenna-coupled photo-detector (Fig.1a). A spectrum analyser is used to monitor the spectral components of the backscatter carrier at 1 GHz (Fig. 1b), which is received and de-modulated (AD8347) by the interrogator placed at a distance (d) from the antenna-coupled photo-detector (Fig. 1c).